Analysis of Distribution Process to the Increasing of Escherichia Coli in Dairy Fresh Milk Products from X Cattle Farm in Surabaya - Nina Emsi Pramesti; Ririh Yudhastuti (Universitas Airlangga, 2017)
Fresh milk was one of food ingredients with high nutrition and widely consumed by people with no processed before consumed so it's easily damaged. This research aims to determine the bacteriological quality of the milk before after distribution, and to analyze an increase of the bacteria Escherichia coli during distribution. The research was an descriptive with observational methods. Subjects were selected by purposive sampling with the number of samples were 4 samples of milk before distribution and 20 samples of milk after distribution of Escherichia coli test. Milk samples were tested before and after the distribution. After distribution during 2 hours, 1 sample was taken every 20 minutes every day during 4 days continuously. Data obtained by interviewing, observing and testing of milk samples to the laboratory. Data were analyzed by descriptive and simple linear regression analysis. The results showed that hygiene and sanitation in the milk process and distributions were not good. The result of laboratory test showed that fresh milk positively contaminated with Escherichia coli was exceeds the standard of microbial contamination in food set by SNI 7389: 2009. The number of Escherichia coli increased during 2 hours for distribution based on a statistical test simple linear regression. Escherichia coli bacterial contamination in milk could be caused from lack of awareness to sanitary hygiene of milk process. Bacteria increased during distribution may be due to lack of good hygiene and sanitation during the distribution process. Therefore it necessary to carry out the processing of milk before the consumption, to monitor the sanitation of the farms by prevent the damage, improve of sanitary and to test the samples of fresh milk regularly for keep a good quality of product.